Introductory essay by Rita Charon - Charon, Rita (Socialmedicinsk tidskrift, 2024)
I am honored to welcome readers into this Special Issue on Narrative Medicine for the Swedish Journal of Social Medicine. We authors propose a storied conception of health care, in full view of the experiences of those who suffer illness and those who are trained to help them. Years ago, a group of clinicians and scholars at Columbia University in New York fashioned an approach to patient care that strengthened the narrative dimensions of illness and care. They named it narrative medicine. Narrative medicine invites ways of knowing from literature, history, and philosophy and creative fields of visual and performative arts into clinical practice. A doctor or nurse or therapist trained in narrative medicine knows how to capture and respond to the account given by a patient and family. They can recognize the possible meanings of what they see and hear and intuit in the words and actions of their patients. They bring humility, curiosity, and unconditional affiliation to patients to their work. As a dividend, they are also equipped to represent their own complex experiences in caring for their patients in words or art work, thereby coming to understand themselves in the process.